Design and analysis of a novel dielectric loaded helical antenna - Ezanuddin, A. A. M.; Soh, Ping Jack; Azremi, Abdullah Al Hadi; R. Badlishah, Ahmad, Assoc. Prof. Dr. (World Scientific and Engineering Academy and Society (WSEAS) Press, 2010)
Link to publisher's homepage at http://www.wseas.org/